An Uncommon Case of Splenic Abscess with Gangrenous Gas Necrosis. (15th January 2022) - Basukala, Sunil; Pathak, Bishnu Deep; Mainali, Gaurab; Rayamajhi, Bikash Bahadur; Mishra, Raveesh; Thapa, Narayan
Abstract : Splenic abscess is a rare clinical entity with diagnostic challenges. Though rare, it is potentially a life-threatening clinical condition with high mortality reaching more than 70%. The common signs and symptoms include the triad of fever, left upper quadrant tenderness, and leukocytosis. Early diagnosis, however, can readily be made by the combination of clinical features, abdominal ultrasonography (USG), and computed tomography (CT). The management of splenic abscess includes medical therapy, CT-guided percutaneous aspiration, and splenectomy. We, hereby, present a rare case of splenic abscess with gangrenous gas necrosis, who underwent splenectomy.